2003
DOI: 10.1093/aje/kwg041
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Cofactors of Hepatitis C Virus-related Hepatocellular Carcinoma: A Prospective Study of 12,008 Men in Taiwan

Abstract: In a community-based prospective study, the authors examined the independent and interactive effects of hepatitis C virus (HCV) infection and cofactors, including hepatitis B virus (HBV) infection and lifestyle habits, on the incidence of hepatocellular carcinoma (HCC) in Taiwan. At baseline recruitment, subjects were evaluated with regard to second-generation HCV antibody (anti-HCV), hepatitis B surface antigen, and serum alanine aminotransferase, as well as cigarette smoking, alcohol drinking, and betel quid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
112
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(125 citation statements)
references
References 44 publications
8
112
0
5
Order By: Relevance
“…Sun et al (2003) suggest that the adjusted relative risk of HCC development was 3.9 for smokers who were positive for anti-HCV in comparison with that for nonsmokers who were negative for anti-HCV. Yu et al (1991) reported that there were significantly synergistic effects of anti-HCV with cigarette smoking.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Sun et al (2003) suggest that the adjusted relative risk of HCC development was 3.9 for smokers who were positive for anti-HCV in comparison with that for nonsmokers who were negative for anti-HCV. Yu et al (1991) reported that there were significantly synergistic effects of anti-HCV with cigarette smoking.…”
Section: Discussionmentioning
confidence: 93%
“…The odds ratio of death from HCC for smoking was 9.60 (1. 50 -61.35) Many studies have reported that chronic hepatitis C virus (HCV) infection is a risk factor for hepatocellular carcinoma (HCC) (Mori et al, 2000;El-Serag, 2002;Sun et al, 2003;Ayoola and Gadour, 2004), HCV appearing to be more hepatocarcinogenic than hepatitis B virus (HBV) (Pang et al, 2005). While alcohol is a well established risk factor for HCC, there is evidence that cigarette smoking is also a risk factor (Mukaiya et al, 1998;Mizoue et al, 2000;Chen et al, 2003), though some studies reported no or an insignificant association (La Vecchia et al, 1988;Evans et al, 2002).…”
mentioning
confidence: 99%
“…Most HCC patients have a chronic liver disease in the background liver, among which chronic viral hepatitis due to hepatitis C virus (HCV) or hepatitis B virus (HBV) is very common [5][6][7]. Surveillance for HCC is now a part of standard clinical practice for patients with chronic viral hepatitis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Taiwan, with high prevalence rates of both cirrhosis and liver cancer, has an increasing rate of betel (Areca catechu) chewing; the nuts are chopped and, with Piper betle vine flower heads, used as betel-chews by a tenth of the 23 million inhabitants currently (2) . This habit is recognized to be carcinogenic in man (2) and has been reported to be associated with LC and with HCC in Taiwan (3)(4)(5)(6) .…”
mentioning
confidence: 99%